Analysis of Obstacles to Completion of Follow-up Recommendations in ABC Regional Government - Hasibuan, Tirmizi Azhar; Wardhani, Ratna (E-Jurnal Akuntansi, 2024)
This study analyzes the obstacles to the completion of follow-up recommendations by the Regional Government of ABC on the Province Inspectorate of XYZ reports. This study aims to determine obstacles in the completion of follow-up recommendations on the Province Inspectorate of XYZ reports. The data collection will be collected using semi-structured interviews with the follow-up team and Regional Apparatus. The data collection will be collected using documentation for the implementation of follow-up. Then this study uses data analysis techniques, namely content analysis. The results of the study indicated that the Regional Government of ABC’s compliance in follow-up recommendations on the Province Inspectorate of XYZ reports is not yet optimal, then the role of Regency Inspectorate of ABC is not yet optimal, and there are obstacles faced by Regional Apparatus in the completion of follow-up recommendations on the Province Inspectorate of XYZ reports which resulted in a low level of follow-up completion.    Keywords: Follow-up Recommendations; Province Inspectorate Reports; Compliance; Role